Tìm x:
\(\sqrt{9x^2+6x+1}=5\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\sqrt{2x}=12\left(đk:x\ge0\right)\)
\(2x=144\)
\(x=72\)
b) \(\sqrt{9x^2-6x}+1=10\)\(\left(Đk:x\le0;x\ge\dfrac{2}{3}\right)\)
\(\sqrt{9x^2-6x}=9\)
\(9x^2-6x=81\)
\(\left(3x-1\right)^2=82\)
\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{\sqrt{82}+1}{3}\\x=\dfrac{1-\sqrt{82}}{3}\end{matrix}\right.\)
c) \(x^2\sqrt{5}-\sqrt{125}=0\)
\(x^2\sqrt{5}=5\sqrt{5}\)
\(x^2=5\)
\(\Rightarrow\left[{}\begin{matrix}x=\sqrt{5}\\x=-\sqrt{5}\end{matrix}\right.\)
a.
ĐKXĐ: \(x\ge-\dfrac{5}{3}\)
\(9x^2-3x-\left(3x+5\right)-\sqrt{3x+5}=0\)
Đặt \(\sqrt{3x+5}=t\ge0\)
\(\Rightarrow9x^2-3x-t^2-t=0\)
\(\Delta=9+36\left(t^2+t\right)=\left(6t+3\right)^2\)
\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{3+6t+3}{18}=\dfrac{t+1}{3}\\x=\dfrac{3-6t-3}{18}=-\dfrac{t}{3}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}t=3x-1\\t=-3x\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}\sqrt{3x+5}=3x-1\left(x\ge\dfrac{1}{3}\right)\\\sqrt{3x+5}=-3x\left(x\le0\right)\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}3x+5=9x^2-6x+1\left(x\ge\dfrac{1}{3}\right)\\3x+5=9x^2\left(x\le0\right)\end{matrix}\right.\)
\(\Leftrightarrow...\)
c.
ĐKXĐ: \(x\ge-5\)
\(x^2-3x+2-x-5-\sqrt{x+5}=0\)
Đặt \(\sqrt{x+5}=t\ge0\)
\(\Rightarrow-t^2-t+x^2-3x+2=0\)
\(\Delta=1+4\left(x^2-3x+2\right)=\left(2x-3\right)^2\)
\(\Rightarrow\left[{}\begin{matrix}t=\dfrac{1+2x-3}{-2}=1-x\\t=\dfrac{1-2x+3}{-2}=x-2\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}\sqrt{x+5}=1-x\left(x\le1\right)\\\sqrt{x+5}=x-2\left(x\ge2\right)\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x+5=x^2-2x+1\left(x\le1\right)\\x+5=x^2-4x+4\left(x\ge2\right)\end{matrix}\right.\)
\(\Leftrightarrow...\)
Ta có :
\(\sqrt{9x^2-6x+2}=\sqrt{\left(9x^2-6x+1\right)+1}=\sqrt{\left(3x-1\right)^2+1}\ge\sqrt{1}=1\)
\(\sqrt{45x^2-30x+9}=\sqrt{5\left(9x^2-6x+1\right)+4}=\sqrt{5\left(3x-1\right)^2+4}\ge\sqrt{4}=2\)
\(\sqrt{6x-9x^2+8}=\sqrt{-\left(9x^2-6x+1\right)+9}=\sqrt{-\left(3x-1\right)^2+9}\le3\)
\(\Rightarrow VT\ge3\ge VP\)
mÀ đề lại cho \(VT=VP\) \(\Rightarrow\hept{\begin{cases}\sqrt{\left(3x-1\right)^2+1}=1\\\sqrt{\left(3x-1\right)^2+4}=2\\\sqrt{-\left(3x-1\right)^2+9}=3\end{cases}\Rightarrow x=\frac{1}{3}}\)
Vậy \(x=\frac{1}{3}\)
a: ĐKXĐ: x>=-3/2
\(\sqrt{x^2+4}=\sqrt{2x+3}\)
=>\(x^2+4=2x+3\)
=>\(x^2-2x+1=0\)
=>\(\left(x-1\right)^2=0\)
=>x-1=0
=>x=1(nhận)
b: \(\sqrt{x^2-6x+9}=2x-1\)(ĐKXĐ: \(x\in R\))
=>\(\sqrt{\left(x-3\right)^2}=2x-1\)
=>\(\left\{{}\begin{matrix}\left(2x-1\right)^2=\left(x-3\right)^2\\x>=\dfrac{1}{2}\end{matrix}\right.\)
=>\(\left\{{}\begin{matrix}\left(2x-1-x+3\right)\left(2x-1+x-3\right)=0\\x>=\dfrac{1}{2}\end{matrix}\right.\)
=>\(\left\{{}\begin{matrix}\left(x+2\right)\left(3x-4\right)=0\\x>=\dfrac{1}{2}\end{matrix}\right.\)
=>x=4/3(nhận) hoặc x=-2(loại)
c:
Sửa đề: \(\sqrt{4x+12}=\sqrt{9x+27}-5\)
ĐKXĐ: \(x>=-3\)
\(\sqrt{4x+12}=\sqrt{9x+27}-5\)
=>\(2\sqrt{x+3}=3\sqrt{x+3}-5\)
=>\(-\sqrt{x+3}=-5\)
=>x+3=25
=>x=22(nhận)
d: ĐKXĐ: \(\left[{}\begin{matrix}x< =\dfrac{3-\sqrt{5}}{4}\\x>=\dfrac{3+\sqrt{5}}{4}\end{matrix}\right.\)
\(\sqrt{4x^2-6x+1}=\left|2x-5\right|\)
=>\(\sqrt{\left(4x^2-6x+1\right)}=\sqrt{4x^2-20x+25}\)
=>\(4x^2-6x+1=4x^2-20x+25\)
=>\(-6x+20x=25-1\)
=>\(14x=24\)
=>x=12/7(nhận)
a: =>2*căn x+5+căn x+5-1/3*3*căn x+5=4
=>2*căn(x+5)=4
=>căn (x+5)=2
=>x+5=4
=>x=-1
b: =>\(6\sqrt{x-1}-3\sqrt{x-1}-2\sqrt{x-1}+\sqrt{x-1}=16\)
=>2*căn x-1=16
=>x-1=64
=>x=65
c, \(\sqrt{\left(x-3\right)^2}-2\sqrt{\left(x-1\right)^2}+\sqrt{x^2}=0\\ \Leftrightarrow\left|x-3\right|-2\left|x-1\right|+\left|x\right|=0\left(1\right)\)
TH1: \(x\ge3\)
\(\left(1\right)\Rightarrow x-3-2x+2+x=0\\ \Leftrightarrow-1=0\left(loại\right)\)
TH2: \(2\le x< 3\)
\(\left(1\right)\Rightarrow3-x-2x+2+x=0\\ \Leftrightarrow-2x=-5\\ \Leftrightarrow x=\dfrac{5}{2}\left(tm\right)\)
TH3: \(0\le x< 2\)
\(\left(1\right)\Rightarrow3-x+2x-2+x=0\\ \Leftrightarrow2x=1\\ \Leftrightarrow x=\dfrac{1}{2}\left(tm\right)\)
TH4: \(x< 0\)
\(\left(1\right)\Rightarrow3-x+2x-2-x-=0\\ \Leftrightarrow1=0\left(loại\right)\)
Vậy \(x\in\left\{\dfrac{1}{2};\dfrac{5}{2}\right\}\)
Trả lời:
\(\sqrt{9x^2+6x+1}=5\)
\(\Leftrightarrow\sqrt{\left(3x+1\right)^2}=5\)
\(\Leftrightarrow\left|3x+1\right|=5\)
\(\Leftrightarrow\orbr{\begin{cases}3x+1=5\\3x+1=-5\end{cases}\Leftrightarrow}\orbr{\begin{cases}3x=4\\3x=-6\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{4}{3}\\x=-2\end{cases}}\)
Vậy \(x\in\left\{\frac{4}{3};-2\right\}\)
Bài làm:
Ta có: \(\sqrt{9x^2+6x+1}=5\)
\(\Leftrightarrow9x^2+6x+1=5^2\)
\(\Leftrightarrow\left(3x+1\right)^2=5^2\)
\(\Leftrightarrow\orbr{\begin{cases}3x+1=5\\3x+1=-5\end{cases}}\Leftrightarrow\orbr{\begin{cases}3x=4\\3x=-6\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=\frac{4}{3}\\x=-2\end{cases}}\)
Vậy tập nghiệm của PT \(S=\left\{-2;\frac{4}{3}\right\}\)
Học tốt!!!!